PERANCANGAN SISTEM INFORMASI APLIKASI PENGELOLAAN DATA ADMINISTRASI WARGA (SIAP WARGA) BERBASIS WEBSITE DENGAN MENGGUNAKAN FRAMEWORK CODEIGNITER - Ghea Aldilla Ayu (2020)
Management of population administration data is an act of the results of registration and civil registration activities carried out regularly. With the increase in birth rates and mortality rates every day, certainly affects the number of population in a region. The population administration information system provides convenience so that recording is no longer done conventionally using stationery. Apart from being inefficient, the data is vulnerable to being lost or damaged, and the data is no longer accurate. This application system can be used from a small level such as on a neighbourhood. There are many people every day who take care of population administration. This makes managers must be responsive in serving their citizens. Based on the above problems, the authors make a web-based system design that is named the Citizen Administration Data Management Application Information System (SIAP Warga). SIAP Warga application is designed using the waterfall method using the CodeIgniter and MySQL framework as a database server. Thus it is hoped that this bureaucratic system will become easier.